Fitting In Affordable Housing in Downtown Toronto - Teti Armiati Argo (The Institute for Research and Community Services, Institut Teknologi Bandung, 1998)
Allocating new low income housing could be challenging particularly in large cities which emphasize profit-making activities. For urban planners in Toronto, selling up government interventions should be conjoined with the Ontario's policy on low income housing, but more importantly, with the nature of provincial politics. When socialist